Initial growth of clonal seedlings of Passiflora mucronata genotypes in response to paclobutrazol concentrations (Research, Society and Development, 2020)
Paclobutrazol (PBZ) is a plant growth regulator of the triazole group that can block the biosynthesis of gibberellic acid, resulting in reduced plant height and increased stem diameter. This study aimed to evaluate the effect of different paclobutrazol concentrations on seedling quality of Passiflora mucronata Lam. Two Passiflora mucronata genotypes were used, one resistant (G5) and one tolerant (G7) to fusariosis, prepared as cuttings treated with PBZ. The experimental design was completely randomized, in a 2 x 4 factorial arrangement corresponding to two genotypes (G5 and G7) and four PBZ concentrations (0, 5, 10, and 15 mg plant-1), with three replications of four plants. Data were subjected to analysis of variance, regression analysis, and the F-test, followed by Pearson’s correlation test between variables. PBZ promoted an increase in the plagiotropic shoot diameter and the leaf area index of genotypes G5 and G7, in addition to increased shoot length in genotype G5 and increased number of leaves in genotype G7. PBZ also resulted in increased photosynthesis and stomatal conductance. There was a positive correlation for genotype G5, between the plagiotropic shoot diameter and the leaf transpiration rate, and for genotype G7, between the plagiotropic shoot diameter and the number of leaves. Genotypes G5 and G7 showed different phenotypic responses when subjected to PBZ doses, highlighting the intraspecific divergence of the species.